Rigorous scheduling of mesh-structure refined petroleum pipeline networks - Cafaro, Diego Carlos (2012)
Pipeline networks represent the major mode of transportation for crude oil and refined fuels. Recent data suggest that this trend will persist in coming years. A multiproduct pipeline network can be described as a set of interconnected pipelines with several input and receiving terminals. In the most general case, it has a mesh-like configuration with alternative paths between two terminals. Pumping and delivery operations should be scheduled all at once in an integrated fashion. This work introduces a novel MILP continuous-time formulation for the scheduling of mesh pipeline networks. The pipeline operational plan is conceived as a sequence of composite pumping runs each one involving at most a batch injection at every input station. The model solution simultaneously provides the timing of batch inputs at every source, the product sequence and lot sizes at every pipeline, and the flows diverted to terminals. Three examples of growing complexity were successfully solved at low CPU times.